Managing future petroleum revenues and establishment of a fiscal rule and a sovereign wealth fund. Green Paper (Government of Guyana, 2018)
This Green Paper details specific issues and points out possible courses of action in terms of policy and legislation. It captures key issues for consideration, including the mechanisms to ensure sustainable use of petroleum revenues to achieve a diversified and green economy, with a specific predisposition to avoid mismanagement of the national patrimony (i.e. "natural resource curse").